2011
DOI: 10.1208/s12249-011-9688-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoporotic Drug Release from Ordered Mesoporous Bioceramics: Experiments and Modeling

Abstract: Abstract. The release of a potent bone-resorption inhibitor such as zoledronate from a versatile drug delivery system such as SBA 15 has been modeled. The initial and boundary conditions have been defined, together with the system parameters, including the determination of equilibrium and transport parameters. Additionally, the experimental model of the same system has been observed to validate the prediction here developed. This approach represents a powerful tool for the designing of mesoporous implantable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…Finally, the bands found at 750, and 480 cm -1 correspond to the flexural vibration of the O-Si-O bond. The bands obtained in the synthesis of SBA-15 are in agreement with other studies reported [44][45][46][47] . Moreover, PLA fibers present characteristic absorption bands at 1,749, 1,460, 1,183, and 1,090 cm -1, which are attributed to C=O stretching vibration, C-H deformation vibration, and C-O-C stretching vibration in PLA 48,49 .…”
Section: Ft-ir Of Pla/sba15 Composite Scaffoldsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the bands found at 750, and 480 cm -1 correspond to the flexural vibration of the O-Si-O bond. The bands obtained in the synthesis of SBA-15 are in agreement with other studies reported [44][45][46][47] . Moreover, PLA fibers present characteristic absorption bands at 1,749, 1,460, 1,183, and 1,090 cm -1, which are attributed to C=O stretching vibration, C-H deformation vibration, and C-O-C stretching vibration in PLA 48,49 .…”
Section: Ft-ir Of Pla/sba15 Composite Scaffoldsupporting
confidence: 91%
“…Moreover, PLA fibers present characteristic absorption bands at 1,749, 1,460, 1,183, and 1,090 cm -1, which are attributed to C=O stretching vibration, C-H deformation vibration, and C-O-C stretching vibration in PLA 48,49 . Finally, the analysis by FT-IR of the PLA/SBA-15 fiber composite shows the adsorption of bands mostly attributed to the PLA and the adsorption of a new band at 480 cm -1 correspondings to the flexural vibration of the Si-O bond, indicating the presence and incorporation of the SBA-15 on the morphology of the fibers 44,46,48 .…”
Section: Ft-ir Of Pla/sba15 Composite Scaffoldmentioning
confidence: 94%
“…The amount of the drug released from HY-5 is almost negligible ($5%) over the period of 300 min. Release profiles for drug molecules adsorbed in porous media can be analyzed using empirical [38] or mechanistic models [39][40][41][42]. In this work, the release profiles were fitted to the first order kinetic model for drug release from a porous matrix [38,43].…”
Section: -Fluorouracil Release From Hy Zeolitesmentioning
confidence: 99%
“…ZOL/SBA-15 release profile denoted that there was a burst desorption at the beginning of the experiment, followed by a more stationary release. After 192 h, it reached to completely release 106,107. The presence of the CNT in the structure of SBA-15 converts it to a conductive composite which allows applying an external electrical stimulus to influence cell biological responses.…”
mentioning
confidence: 99%